Performance-Based Funding of Higher Education: the First Ukrainian Experiences - Denys Svyrydenko (International Society of Philosophy and Cosmology (ISPC), 2021)
The article investigates the global approach to comprehending the concept of performance-based funding (PBF) of higher education. The authors briefly describe the history and the variety of existing PBF models across the globe and determine core differences between them. The article also characterizes the modern Ukrainian public policy of implementing the performance-based funding of higher education and highlights both the relevant merits and of the national PBF model and priority issues of its further development.